Weaponizing Information: The Rise of Social Media Manipulation in Nepal - Bhandari, Bhuwan (Journal of Durgalaxmi, 2024)
The internet presents considerable challenges to democratic processes, particularly through social media platforms such as Meta and Twitter. These platforms frequently create environments where users are confined to echo chambers, thereby reinforcing homogeneous viewpoints and exacerbating societal divisions. As of May 2024, approximately 15.4 million individuals in Nepal were reported to be online, with 13.5 million engaging in social media activities—representing 49.6% of the population—through various forms of content that express both personal and collective experiences. A 2020 report from the Pew Research Center highlights that 64% of American adults perceive that misinformation significantly muddles public comprehension of contemporary issues. This phenomenon of echo chambers not only distorts public sentiment but also aids in the proliferation of conspiracy theories through algorithmic recommendations, thereby eroding constructive discourse across differing ideological perspectives. In Nepal, significant events have triggered the dissemination of damaging rumors on social media, which are often weaponized for personal vendettas. This study examines these incidents as a particular case and aims to confront the perils linked to the manipulation of information. To investigate the exploitation of viral content that caters to entrenched interests and deepens societal rifts, the research employs case studies, narrative inquiry, and content analysis. It underscores the pressing necessity for legislative reforms, improved enforcement mechanisms, and proactive engagement from stakeholders to foster the ethical and equitable utilization of social media for the greater good of society.